The Effectiveness of a Training Program for Reducing Speech Disorders Among Kindergarten Children - Suleiman Suleiman, Naji; Shukri, Bewar (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: This study aimed to develop and evaluate a comprehensive training program for reducing speech disorders among Kurdish-speaking kindergarten children, and to examine differences in parental evaluations of intervention outcomes. Despite the critical importance of early intervention for speech disorders, research in the Kurdistan Region is extremely limited, creating a significant gap in culturally and linguistically appropriate intervention approaches for Kurdish-speaking children. Methods: Using a quasi-experimental pre-test/post-test design, children with speech disorders were divided into experimental and control groups, with the experimental group receiving a training program over eight weeks while the control group received no intervention. Assessment was conducted using a validated speech disorders scale measuring pronunciation, fluency, voice, expressive and receptive language, and social-linguistic interaction. Results: Statistical analysis revealed significant improvements in the experimental group across all dimensions with large effect sizes, and significant differences between experimental and control groups in post-test scores. Parental evaluations showed high consistency, with only minor discrepancies between fathers’ and mothers’ assessments in specific dimensions. Conclusion: These findings demonstrate the efficacy of structured, comprehensive early interventions for speech disorders in Kurdish-speaking kindergarten children, highlighting the importance of culturally adapted intervention approaches and suggesting that similar programs should be implemented in educational settings throughout the region.